Masalah-Masalah Kritis Siswa SMA dalam Menyelesaikan Soal Pertidaksamaan Aljabar - MUSTAQIM MUSTAQIM; M IKHSAN; RAHMAH JOHAR (Universitas Syiah Kuala, 2019)
Abstract: This study aimed to describe the critical problems experienced by students in solving algebraic inequalities. The subjects of the study were nine Year 12 students from one of the senior high school in Banda Aceh and students studying at one of the tuition centres in Banda Aceh, Indonesia. The data was gathered through algebraic inequality test followed by interviews. The results showed that the critical problems experienced by students in solving the question of algebraic inequality were problems in understanding cross-multiplication requirements, in applying cancellation rules, in understanding the definition area and value areas of a function, in determining exponential inequalities, and in understanding the definition of absolute value.Keywords: critical problems, difficulties, algebraic inequalities.